PSYCHOLINGUISTIC ANALYSIS OF THE VERBAL AND NONVERBAL PRESENTATIONS IN THE ANIMATED CARTOON “HORRID HENRY” - Tkachenko , Nataliya (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2022)
The article accounts on the psycholinguistic semantics of the verbal and nonverbal children’s representations thus reflecting the everlasting problem of children upbringing. The animated cartoon “Horrid Henry” has not yet been chosen as the material for the polyparadigmal psycholingustic study of communication, comprising lexicosemantic, linguocognitive, pragmalinguistic and linguodidactic analyses. The cоmplex investigation of the collocation “Horrid Henry” comprised lexicosemantic, contextual and textual analyses. The object of the article is the dialogical speech in the children’s animated cartoon television series “Horrid Henry. The subject matter of the research is the linguistic and conceptual semantics of the title “Horrid Henry”. The novelty of the research is represented both by the material and by the psycholinguistic functional paradigmal methods applied as psycholinguistic studies are inseparable from other branches of linguistics. The article is aimed at interpreting and classifying the motives of the child’s misbehavior in verbal and nonverbal psycho-semantic representations, The purpose of the article is reflecting the pluses and minuses of communication adults-children and their far-going influence on society. The key notion “horrid” forms the complex concept of subjective egotism that can be attributed to the child’s sub-consciousness and his search for the social recognition. The functional paradigm revealed the fact that it is useful activity rather than the parents’ instructions or adaptation to society that organizes the child’s mind and behavior. Thus, the title “Horid Henry” loses its semantic “horid”, revealing positive conceptual transformations. __________ References: • Kapustiuk, O. M., Pastushenko, V. S. «Psykhologichny osoblivosty samopresentatsiinoi povedinki ditey 9-10 rokiv.» Оsоbistist w ymovakh krizovih viklikiv suchasnosti бистість в умовах кризових викликів сучасності: Маterialy metodologichnoho seminaru NAPN Ukraini 24 beresnia 2016 roku (Кyiv, 2016): 146−153. • Komens’kyj, Ja. Velyka dydaktyka (1982): 309−311. • Ushinsky, K. D. «Ludina yak predmet vikhovannia.» Vibrany ped. Tvory u 2 t., т. 1 (Kyiv, Radyanska shkola, 1983), 393. • Fitsula, М. М. Pedagogika. Navchalny posibnik dla studentiv vischikh pedagogichnih zakladiv (Кyiv, Vidavnichiy Tsentr “Akademiya”, 2002). 528. • Bolshoi entsiklopedichesky slova, https://rus-big-enc-dict.slovaronline.com/54516 • “HorridHenry” animated cartoon, https://en.wikipedia.org/ wiki/ Horrid _Henry_ (TV_series). • Oxford Advanced Learner’s Dictionary, https://www.oxfordlearnersdictionaries. com/definition/ english/horrida rather horrid little man • Oxford Advanced American Dictionary, https://www.oxfordlearnersdictionaries. com/ definition/ american_english/horrid